Multi-objective economic emission dispatch of thermal power plants based on grey relational analysis and analytic hierarchy process. Issue 5 (August 2020) - Chen, Shiyi; Chen, Wei; Soomro, Ahsanullah; Luo, Lijuan; Xiang, Wenguo
In this paper, mathematical models for a synthesized evaluation were established according to grey relational analysis and analytic hierarchy process. The models were used to select a power dispatch scheme considering hierarchies of material consumption, electrical efficiency, exergy efficiency, and environmental benefit. Four unit dispatch schemes, i.e., proportional fair allocation dispatch, conventional economic dispatch, economic emission dispatch, and economic emission dispatch with varied weights were investigated and compared. Analytic hierarchy process decision-making approach has been employed to find the optimal Pareto solution as the best tradeoff between cost and pollutant emission. The model indicated that the economic emission dispatch was preferred as the best option and could further reduce fuel consumption and pollutant emission, followed by the economic emission dispatch with varied weights. The assessment performed serves decision makers a valuable reference for policy making in the power dispatch sector.